1975
DOI: 10.1177/000348947508400510
|View full text |Cite
|
Sign up to set email alerts
|

Extraluminal Foreign Bodies (Coins) in the Food and Air Passages

Abstract: Four children with foreign bodies found outside the lumen of the upper food and air passages are presented. The diagnostic difficulty of such extraluminal foreign bodies and the importance of accurate localization by endoscopy and radiologic examination prior to external surgical removal are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
1

Year Published

1982
1982
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 3 publications
1
8
0
1
Order By: Relevance
“…Once the diagnosis has been confirmed, cervical or thoracic exploration is undertaken. As in the literature opening of the esophagus is unnecessary [2,14,15]. The foreign body is easily found in a mass of inflammatory tissue as in our case.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Once the diagnosis has been confirmed, cervical or thoracic exploration is undertaken. As in the literature opening of the esophagus is unnecessary [2,14,15]. The foreign body is easily found in a mass of inflammatory tissue as in our case.…”
Section: Discussionsupporting
confidence: 59%
“…This is characteristic for an extruded foreign body. Despite all of the drastic possibilities associated with treatment of esophageal perforations, our approach and that found in the literature [2,14,15] have been quite simple. Once the diagnosis has been confirmed, cervical or thoracic exploration is undertaken.…”
Section: Discussionmentioning
confidence: 96%
“…The described complications include mediastinitis with or without abscess, 6,22 esophageal-airway fistulas, 23,24 esophageal-vascular fistulas 6,22,25 extraluminal migration of object, 24,[26][27][28][29] and false diverticula. 28 In the available literature from the 1970s to the present, most studies demonstrated an injury rate of about 1%, with 1 review reporting 0.1% 18 and several smaller studies as high as 4% to 6%.…”
Section: Discussionmentioning
confidence: 99%
“…The first patient had a previously repaired congenital tracheo-oesophageal fistula and his ingested coin was lodged at the site of the repair and had eroded partly into the right bronchus and partly into the mediastinal tissue; postoperatively the fistula re-opened but closed spontaneously within four weeks. 4 The other postoperative complication was a small posterior oesophageal fistula, which closed after two weeks of conservative management. 7 In our case there was a small postoperative leak that meant that the child was not able to resume oral feeds for a few weeks.…”
Section: Discussionmentioning
confidence: 99%